2009
DOI: 10.1016/j.cocis.2009.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering near and from interfaces using evanescent wave and ellipsometric light scattering

Abstract: The broad range of interface light scattering investigations in recent years shows the power and the versatility of these techniques to address new and open questions in colloid and interface science and the soft condensed matter field. Structural information for polymers, liquid crystals, or colloids close to planar or spherical colloidal interfaces are either captured with long range light scattering resolution, or in a complementary approach by high resolution ellipsometric techniques. Of special interest i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 106 publications
1
29
0
Order By: Relevance
“…39 Evanescent wave dynamic light scattering 10 combines the advantages of dynamic light scattering (DLS), i.e., statistical averaging and fast detection with a localized probing due to the short penetration depth, κ −1 , of an evanescent wave that is produced under total internal reflection conditions at an interface. 9 However, the interpretation of the measured intensity time autocorrelation function (TCF), g (2) (q, t; κ) = I (q, t; κ)I (q, 0; κ) / I (t) 2 , is far from trivial as it incorporates both confinement effects and the specific evanescent wave illumination that is decaying exponentially in space away from the solid-liquid interface. In the dilute limit, g (2) (q, t; κ) was originally calculated by Lan et al 10 taking into account the evanescent geometry and the wall mirror effect, while its initial decay incorporating the anisotropic viscous drag effect as a function of distance from the wall was more recently calculated by Holmqvist et al 14,28,40 With increasing volume fraction (φ), particle-particle HIs become important and modify the wall-induced drag effect.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Evanescent wave dynamic light scattering 10 combines the advantages of dynamic light scattering (DLS), i.e., statistical averaging and fast detection with a localized probing due to the short penetration depth, κ −1 , of an evanescent wave that is produced under total internal reflection conditions at an interface. 9 However, the interpretation of the measured intensity time autocorrelation function (TCF), g (2) (q, t; κ) = I (q, t; κ)I (q, 0; κ) / I (t) 2 , is far from trivial as it incorporates both confinement effects and the specific evanescent wave illumination that is decaying exponentially in space away from the solid-liquid interface. In the dilute limit, g (2) (q, t; κ) was originally calculated by Lan et al 10 taking into account the evanescent geometry and the wall mirror effect, while its initial decay incorporating the anisotropic viscous drag effect as a function of distance from the wall was more recently calculated by Holmqvist et al 14,28,40 With increasing volume fraction (φ), particle-particle HIs become important and modify the wall-induced drag effect.…”
Section: Introductionmentioning
confidence: 99%
“…7 Under such confined conditions, near surfaces, interfaces, and in microchannels, particle dynamics are affected both by direct enthalpic interactions 8 as well as excluded volume and hydrodynamic interactions (HI). 9 While the former are system specific and depend on the specific interaction energy between the moving particles/polymers and the surfaces/interfaces, HI are expected to depend generically on the a) Author to whom correspondence should be addressed. Electronic mail:…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the signal could be the result of interactions between droplets in the bulk of the emulsion but also between droplets and the surface in contact. Indeed, Sigel (2009) reported that evanescent wave light scattering enables to evidence changes in the diffusion of colloids at solid interface due to wall drag effect.…”
Section: Contribution Of Cell Surface Properties To Emulsion Destabilmentioning
confidence: 99%
“…EWDLS measurements on the diffusion of "furry disks" formed by diblock copolymers on top of a water-air interface were reported by Lin, Rice, and Weitz [13]. A recent review provides an overview on further EWDLS investigations [14].…”
Section: Introductionmentioning
confidence: 96%